Coconut water assisted green synthesis of silver nanoparticles - Erusan Kuppan Elumalai; Karuppsamy Kayalvizhi; Simon Silvan (Wolters Kluwer Medknow Publications, 2014)
Aim of the Study: The synthesis, characterization and application of biologically synthesized nanomaterials are an important aspect in nanotechnology. Materials and Methods: The present study deals with the synthesis of silver nanoparticles (Ag-NPs) using the coconut water (C. nucifera) as the reducing agent. The formation of Ag-NPs was characterized by UV-Visible Spectroscopy, Scanning Electron Microscopy (SEM), EDX, X-ray Diffraction (XRD) and FTIR spectroscopy. Results: The synthesized Ag-NPs were predominately polydispersed. Crystalline nature of the nanoparticle in the face centered cubic (fcc) structure are confirmed by the peaks in the XRD pattern corresponding to (111), (200), (220) and (311) planes. Fourier Transform Infra-Red (FT-IR) spectroscopy analysis showed that the synthesized nanoparicles was capped with bimolecular compounds which are responsible for the reduction of silver ions. Conclusion: The approach of green synthesis appears to be cost efficient, ecofriendly and easy alternative to conventional methods of silver nanoparticle synthesis.